Bodyweight categories in weightlifting - Flores, F. J.; Redondo, J. C. (EWF Scientific Magazine, 2017)
Body weight categories in weightlifting. Comparing results of the Olympic Games and World and European Championships from 2005 to 2016. The main goal of this article is to make a descriptive analysis category by category of the results of the Olympic Games (OG) and World and European Championships (WC and EC) since 2005, when the competition rules set a minimal progression of 1.0 kg after any successful attempt for the same athlete, until the 2016 Olympic Games celebrated in Rio. The idea behind this descriptive analysis is to take a snapshot of the last results during the most important competitions for the European weightlifting, observing the best and worst categories and competitions and the trend of results during the period studied (2005-2016). The snapshot presented in this work is a brief study which compares the results obtained in the Olympic Games and World and European Championships since the technical regulation of progression load was changed in 2005. Some of the conclusions that can be drawn from this analysis are: o For men, the tendency shows how the highest results are obtained in 85 kg categories and the lowest outcomes are achieved by the light weight divisions 62 kg and specially 56 kg. o For women, the variability among categories and competitions is higher than men, finding usually the highest results in 75 kg category and clearly occupying the lowest position for p75 kg category. o As for the best results obtained by type of competition, these are usually achieved during the OG closely followed by the WC and clearly below we find with the results obtained in the EC. o Tendency of performance by competitions: for men and the top 3 analyses, trend line shows how the performance is increased throughout the different editions of the OG and WC, showing a clear decrease tendency for EC. On the other hand, studying the tendency of the top 10 ranked athletes the performance in EC and WC is increased and is a plateau for OG. o Tendency of performance by competitions: for women, the trend line shows the same pattern of behavior as in the case of men for EC and WC. For OG the tendency of the results is shown stable with a slight downward trend. This comparison of body weight categories and competitions allows to compare the differences performances obtained between categories, competitions and editions since 2005, when the competition rules set a minimal progression of 1.0 kg after any successful attempt for the same athlete.